The Efforts to Increase Breast Milk Production Through Hypnobreastfeeding In Pakisaji Sub District Malang Regency - Utami, Siska Neeri; Rohmah, Miftakhur; Tuszahroh, Nasifah (Journal of Global Research in Public Health, 2018)
Breast milk is the first, main, and best food for babies, which is scientific. Breast milk contains various nutrients needed in the process of growth and development of babies. Breast milk production can also be increased by hypnobreasfeeding relaxation. Hypnobreasfeeding helps mothers to relax their bodies, and a great way to encourage mindsets in their babies. The purpose of the study was to determine the effect of hypnobreasfeeding on increasing ASI production at pakisaji sub-district Malang district. The population is 25 respondents and the sampling technique used is total sampling with One group pre-post test design. Analysis of the data with the T-test using SPSS for Windows obtained Sig = 0,000, so 0,000 <0,05, which means H1 was accepted. Before hypnobreasfeeding, the average volume of ASI that came out was 163.2 ml, after being treated evenly. the average breast milk volume increased to 462.3 ml and there was an increase in the volume of breast milk by 300 ml. So that there is the influence of hypnobreasfeeding on increasing ASI production at BPM Sri Wahyuning Amd Keb Pakisaji Malang Regency. Based on the results of the study the authors suggest that breastfeeding mothers be more concerned and mothers are not stressed so that mothers can breastfeed calmly